Novel emboli protection cannula during cardiac surgery: first animal study. (January 2014) - Shani, Liran; Cohen, Oved; Beckerman, Ziv; Nir, Rony-Reuven; Bolotin, Gil
Background: Stroke after open heart surgery is a major cause of morbidity and mortality. Up to 60% of intraoperative cerebral events are caused by emboli generated by manipulations of the aorta during surgery. This is the first animal study evaluating the safety and efficacy of a novel aortic cannula designed to extract solid and gaseous emboli during cardiac surgery. Methods: Seven domestic pigs were connected to cardiopulmonary bypass using a CardioGard 24F aortic cannula. Three pigs that were cannulated with a standard aortic cannula were defined as controls. Several main flow and suction regimens were carried out. Osseous particles of different sizes were injected into the proximal aorta to simulate emboli. Results: The CardioGard cannula demonstrated an overall emboli retrieval rate of 77%. A rate of 88.45% was demonstrated during the low-flow regimen used clinically during aortic manipulation. Gaseous and solid emboli were eliminated by suction, as demonstrated by epi-carotid ultrasound. No significant changes were observed in hemodynamic and laboratory parameters. Conclusions: The CardioGard cannula is as simple to use as a regular commercially available aortic cannula, having a similar safety profile and proven efficacy in capturing intraoperative emboli.